The last ISLAnd standing an amphibious landscape planning of Tanza, Navotas - Guerrero, Jo Lyle L. (College of Architecture, University of the Philippines Diliman, 2018)
According to NASA (2015), the rise of sea levels is inevitable in the coming years. Due to climate change & global warming, the rate of rise is increasing. Philippines being an archipelagic country is heavily affected by this. According to research by the University of the Philippines (2015), more than 167 ,000 hectares of coast land will submerge. Tanza, Navotas is considered one of the first areas to submerge. The concept of transhumanism was used to aid and understand the needs of the people in the face of sea level rise. Maslow's Hierarchy of Needs was used to be the model for identifying the needs to improve the community. In order to understand the sea level profile and community profile, projection maps were generated through Project NOAH and a focus group discussion and fuzzy cognitive mapping were done respectively. With these data, a planning framework that included projecting scenarios was done. A 2040 Environmental Restoration + Barrier Landscape Plan was then proposed to address these needs of the people and the environment in the coming years. Amphibious management strategies were proposed to help the environment shift from 2020- 2040. The 2040 Plan is flexible and will adapt through the coming years. In conclusion, the 2040 Environmental Restoration + Barrier Plan addressed the issue of the surrounding communities when it comes to flooding, sea level rise, and unproductive fishponds. Lastly, Tanza Community achieved an extended memory through improving the environment of their landscape.